Pengaruh Citra Merek dan Kualitas Produk terhadap Loyalitas yang Dimediasi oleh Kepuasan - Scorina Dwiantari (STIE Widya Manggala, 2020)
The purpose of this study was to determine the effect of brand image and product quality on consumer loyalty with consumer satisfaction as a mediator using Indrakila Cheese products. To determine the effect of brand image, product quality and customer satisfaction on costumer loyalty using Indrakila Cheese products. To find out whether costumer satisfaction mediates the influence of brand image and product quality on costumer loyalty using Indrakila Cheese products. The population in this study were all costumers who use Indrakila Cheese products. The sample is determined by the Purposive Sampling method. Sampling with Slovin formula obtained 110 respondents. The data used are primary data using a questionnaire. Data analysis using linear regression. Based on the results of the research that has been done, it can be known brand image has a positive effect on costumer satisfaction of Indrakila Cheese products. Product quality has a positive effect on costumer satisfaction of Indrakila Cheese products. Brand image has a positive effect on costumerr loyalty of Indrakila Cheese products. Product quality has a positive effect on costumer loyalty of Indrakila Cheese products. Customer satisfaction has a positive effect on costumer loyalty of Indrakila Cheese products. Brand image has a positive effect on costumer loyalty mediated by costumer satisfaction. Product quality has a positive effect on costumer loyalty mediated by costumer satisfaction.